2020
DOI: 10.4046/trd.2020.0025
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Korean Version of the Bronchiectasis Health Questionnaire

Abstract: Background: The Bronchiectasis Health Questionnaire (BHQ) is a simple and repeatable, self-reporting health status questionnaire for bronchiectasis. We have translated the original version of the BHQ into Korean using a standardized methodology. The purpose of this study was to assess the validity of the Korean version of the BHQ (K-BHQ) with Korean patients. Methods: Stable state patients with bronchiectasis from two academic hospitals were enrolled in this study. The validity was assessed by investigating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The BHQ is comprised of 10 items, with higher scores indicating a better quality-of-life [ 17 ]. A Korean version of the BHQ that was validated in Korean patients with bronchiectasis was used [ 18 ]. Fatigue was assessed using the Korean version of the Fatigue Severity Score (FSS) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The BHQ is comprised of 10 items, with higher scores indicating a better quality-of-life [ 17 ]. A Korean version of the BHQ that was validated in Korean patients with bronchiectasis was used [ 18 ]. Fatigue was assessed using the Korean version of the Fatigue Severity Score (FSS) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…A consensus definition was used to determine bronchiectasis exacerbation and defined as deterioration in three of the following symptoms for at least 48 h: (1) cough; (2) sputum volume increase and/or consistent change; (3) sputum purulence; (4) dyspnoea and/or exercise intolerance; (5) fatigue and/or malaise; or (6) haemoptysis [ 21 ]. This study also used the following measurement tools related to health-related quality of life: the validated Korean version of the Bronchiectasis Health Questionnaire (BHQ) for quality of life, Patient Health Questionnaire 9 for depression, and Fatigue Severity Score for fatigue [ 3 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…(3) sputum purulence; (4) dyspnoea and/or exercise intolerance; (5) fatigue and/or malaise; or (6) haemoptysis [21]. This study also used the following measurement tools related to health-related quality of life: the validated Korean version of the Bronchiectasis Health Questionnaire (BHQ) for quality of life, Patient Health Questionnaire 9 for depression, and Fatigue Severity Score for fatigue [3,22].…”
Section: Assessmentsmentioning
confidence: 99%
“…The translated questionnaires included: QOL-B, BHQ, SGRQ, LCQ, CAT, SOLQ, and SF-36. An additional 14 studies were included since the original review: translated QOL-B was used in Spain (Olveira et al, 2014a, Doña et al, 2018, Máiz et al, 2018, Germany (Ringshausen et al, 2018, Sokol et al 2019 and Brazil (De Camargo et al, 2020); BHQ in Denmark (Gissel et al, 2020) and Korea (Kim et al, 2020); SGRQ in Egypt (Abd-Elazeem et al, 2018), China (Gao et al, 2014b); LCQ in Spain (Máiz et al, 2018), Turkey (Ozalp et al, 2019, Cakmak et al, 2020 and China (Gao et al, 2014b); SOLQ in Turkey (Bulcun et al, 2015); and SF-36 in Turkey (Bekir et al, 2017). All of these studies reported or referenced a validation of the translated questionnaire.…”
Section: Appendixmentioning
confidence: 99%